2019
DOI: 10.1371/journal.pone.0212794
|View full text |Cite
|
Sign up to set email alerts
|

Peer-teaching cardiac ultrasound among medical students: A real option

Abstract: IntroductionTeaching cardiac ultrasound (CU) image acquisition requires hands-on practice under qualified instructors supervision. We assessed the efficacy of teaching medical students by their previously trained classmates (teaching assistants [TAs]) compared to teaching by expert trainers (cardiologists or diagnostic medical sonographers.MethodsSixty-six students received 8-hour CU training: 4-hour lectures on ultrasound anatomy and imaging techniques of 6 main CU views (parasternal long [PLAV] and short axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Students from the post-course group achieved a higher total score (10 [6-12] vs. 5 [3][4][5][6][7][8]; P = 0.001) respectively, image score (5 [4-6] vs. 2 [1][2][3][4]; P = 0.001) and description score (5 [2-6] vs. 2 [2][3][4]; P = 0.01) than the control group. As few as 5 (20%) students from the control group reached >56% of points (9 or more points) of correct answers, whereas in the experimental group it was 14 (56%) students (P = 0.008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students from the post-course group achieved a higher total score (10 [6-12] vs. 5 [3][4][5][6][7][8]; P = 0.001) respectively, image score (5 [4-6] vs. 2 [1][2][3][4]; P = 0.001) and description score (5 [2-6] vs. 2 [2][3][4]; P = 0.01) than the control group. As few as 5 (20%) students from the control group reached >56% of points (9 or more points) of correct answers, whereas in the experimental group it was 14 (56%) students (P = 0.008).…”
Section: Resultsmentioning
confidence: 99%
“…The role of echocardiography in emergency departments has been recently acknowledged [2,3]. Therefore, providing future physicians with skills on how to acquire and interpret cardiac-echo data is becoming highly expected in medical curricula [4][5][6]. To meet these expectations the Board of the Faculty of Medicine of the Jagiellonian University Medical College (JUMC), supported by recent literature on online teaching [7][8][9] and by the experience of successful implementation of ECG e-learning [10,11], introduced in 2020/2021 academic year a subject entirely dedicated to this field.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study using a 4-h PCCU lecture coupled with a 4-h hands-on session revealed that peer instructors were superior to staff instructors (cardiologists or diagnostic medical sonographers) at teaching the scanning techniques. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study using a 4-h PCCU lecture coupled with a 4-h hands-on session revealed that peer instructors were superior to staff instructors (cardiologists or diagnostic medical sonographers) at teaching the scanning techniques. 45 Another study evaluating the ability of first year medical students to generate 7 cardiac views after an educational intervention showed that they only acquired limited scanning skills. The educational intervention involved 16 hours of training over 8 weeks.…”
Section: Image Generationmentioning
confidence: 99%
“…These in-person training programs are essential to reducing the risk of infection among providers. Recently, peer-led training to improve clinical skills or service delivery has shown equal or greater impact than traditional ‘expert-led’ training programs [ 37 , 38 ]. Peer-led training can increase intrinsic motivation, alleviate health care provider teaching burden, and provide accessible role models for learners [ 39 ].…”
Section: Introductionmentioning
confidence: 99%